EDITORIAL CARTOONS USED TO PRESENT IMPLIED MEANING RELATED TO HONG KONG EXTRADITION BILL PROTESTS - Deli Nirmala; Nada Rasyida Rani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
. [Editorial Cartoons Used to Present Implied Meaning Related to Hong Kong Extradition Bill Protests]. In communication, people may express their meaning implicitly. They use different forms of expressions but mean the same thing. The expressions used are not always vocal symbols or linguistic ones but also nonvocal symbols like cartoons. The cartoons can also be the context of the vocal symbols like in this study. This research aims to investigate the implied meaning (implicature) used in the editorial cartoons of the Hong Kong Extradition Bill. To study this, non-participant observation was used to collect the data. There were 12 editorial cartoons on the Taipei Times news website. Using Relevance Theory, the writers analyzed the data using referential, inferential, and pragmatic methods to uncover the implied meaning of the editorial cartoons. The results indicate that the journalist uses the implied meaning or implicature of the editorial cartoons to criticize, forewarn, and provide information. The meaning can be figured out since background knowledge can be used to decode the meaning transmitted. Besides, the context of the situation plays an important role to understand the meaning.